Spontaneous Recovery of the Vestibulo-Ocular Reflex After Vestibular Neuritis; Long-Term Monitoring With the Video Head Impulse Test in a Single Patient - McGarvie, Leigh Andrew; MacDougall, Hamish Gavin; Curthoys, Ian S.; Halmagyi, Gabor Michael (Frontiers in Neurology, 2020)
Vestibular rehabilitation of patients in whom the level of vestibular function is continuously changing requires different strategies than in those where vestibular function rapidly becomes stable: where it recovers or where it does not and compensation is by catch-up saccades. In order to determine which of these situations apply to a particular patient, it is necessary to monitor the vestibulo-ocular reflex (VOR) gains, rather than just make a single measurement at a given time. The video Head Impulse Test (vHIT) is a simple and practical way to monitor precisely the time course and final level of VOR recovery and is useful when a patient has ongoing vestibular symptoms, such as after acute vestibular neuritis. In this study, we try to show the value of ongoing monitoring of vestibular function in a patient recovering from vestibular neuritis. Acute vestibular neuritis can impair function of any single semicircular canal (SCC). The level of impairment of each SCC, initially anywhere between 0% and 100%, can be accurately measured by the vHIT. In superior vestibular neuritis the anterior and lateral SCCs are the most affected. Unlike after surgical unilateral vestibular deafferentation, SCC function as measured by the VOR can recover spontaneously after acute vestibular neuritis. Here we report monitoring the VOR from all 6 SCCs for 500 days after the second attack in a patient with bilateral sequential vestibular neuritis. Spontaneous recovery of the VOR in response to anterior and lateral SCC impulses showed an exponential recovery with a time to reach stable levels being longer than previously considered or reported. VOR gain in response to low-velocity lateral SCC impulses recovered with a time constant of around 100 days and reached a stable level at about 200 days. However, in response to high-velocity lateral SCC and anterior SCC impulses, VOR gain recovered with a time constant of about 150 days and only reached a stable level towards the end of the 500 day monitoring period.